Teaching Simulation Literacy in Adult Healthcare Education: A Qualitative Action Research Study - Elizabeth Sinz; Sally Rudy; Margaret Wojnar; Tammi Bortner (Adult Education Research Conference, 2014)
Teaching and learning with simulation is an increasingly important strategy of adult education in healthcare. This paper discusses the process and results of an action research study on developing a simulation instructor program where experiential learning was not only the topic, but the tool by which the learners received instruction.